Edukasi Perilaku Hidup Bersih Dan Sehat (PHBS) Pada Anak-Anak di Kampung Pemekaran Mister Ngiosi Manokwari Pada Masa Pandemi Covid-19 - Kawulur, Elda Irma Jeanne Joice; sinuraya, Sabarita; dwiranti, febriza; Panjaitan, Rawati; Ratnawati, Sita (IGKOJEI: Jurnal Pengabdian Masyarakat, 2021)
Clean and Healthy Lifestyle (PHBS) are all health behaviors that are carried out with awareness so that family or family members can help themselves in the health sector and play an active role in health activities in the community. This community service program is motivated by limited access to information, transportation and health in rural areas of Kampung Pemekaran Mister Ngiosi Manokwari causing a lack of understanding and application of a clean and healthy lifestyle by children, especially during the Covid-19 pandemic. To overcome this gap, it is necessary to disseminate information about clean and healthy living behavior in children. Activities on PHBS are using interactive learning in the form of lectures and giving some questions related to the PHBS and reward, demonstration related to preventing the transmission of Covid-19. The results of the activity showed that about 80% of the children could carry out 11 steps of hand washing activity well. In terms of healthy food, 100% of the children finished the given food.